Parathyroid Hormone and Glycemic Profile in Healthy Overweight and Obese Adults. (29th May 2020) - Cheung, May; DeLuccia, Rosemary; Altasan, Asma; Al-Ani, Sumer; Parekh, Rushali; Sukumar, Deeptha
Abstract: Objectives: Elevated serum parathyroid hormone concentration (sPTH) is associated with higher prevalence of cardiometabolic diseases. The objective of this study was to examine the differences in cardiometabolic parameters in overweight or obese (Owt/Ob) individuals categorized into a low and high PTH group. Methods: A total of 116 Owt/Ob men and women with a body mass index (BMI) between 24.7 to 43.2 kg/m 2 and ages 20 to 70 years participated in this study. Blood samples were obtained for analyses of sPTH, serum 25-hydroxyvitamin D (s25OHD), serum ionized magnesium (iMg), inflammatory cytokines, insulin, fasting glucose, and triglyceride. Body composition information was measured using dual energy x-ray absorptiometry (DXA). Participants were categorized into either a Low PTH Group (sPTH < 55pg/mL) and High PTH Group (sPTH ≥55pg/mL). Results: The mean sPTH in the Low PTH Group was 39.8pg/mL ± 10.0 (age = 33.5years ± 11.3, BMI = 28.9 kg/m 2 ± 3.4), and in the High PTH Group was 79.5pg/mL ± 19.9 (age = 40.7years ± 12.5, BMI = 29.5/m 2 ± 4.6). The High PTH Group had a higher fat mass % (36.7% ± 8.4, P  = 0.029) and lower lean mass % (59.8% ± 7.9, P  = 0.015) compared to the Low PTH Group (33.0% ± 9.7; 63.7% ± 9.1 respectively). After controlling for age, fasting blood glucose was significantly higher ( P  = 0.024) in the High PTH Group (97.6 mg/dL ± 3.1SEM) compared to the low PTH group (97.6 mg/dL ± 2.9SEM). There were no differences between BMI, body composition, s25OHD, iMg, inflammation cytokines, insulin, and triglyceride between PTH groups after controlling for age. Conclusions: Higher sPTH was associated with a higher fasting glucose in Owt/Ob, but otherwise healthy adults. Attempts to lower sPTH in this population may delay the onset of metabolic conditions and should be explored in prospective studies. Funding Sources: American Heart Association, Drexel University College of Nursing and Health Professions.